2015
DOI: 10.1259/bjr.20140540
|View full text |Cite
|
Sign up to set email alerts
|

Radiology of cardiac devices and their complications

Abstract: This article familiarizes the reader with several different cardiac devices including pacemakers and implantable cardioverter defibrillators, intra-aortic balloon pumps, ventricular assist devices, valve replacements and repairs, shuntoccluding devices and passive constraint devices. Many cardiac devices are routinely encountered in clinical practice. Other devices are in the early stages of development, but circumstances suggest that they too will become commonly found. The radiologist must be familiar with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Current literature describes other cases of anatomical variants which necessitated unusual placement of the wires. For example, entering the left ventricle because of dextro transposition of the great arteries after a Senning/Mustard repair or having to pace the right atrium/ventricle from a persistent left sided superior vena cava and the coronary sinus [5]. There were no other similar case reports or research data describing a patient with an elevated left hemidiaphragm leading to a challenging PPM implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature describes other cases of anatomical variants which necessitated unusual placement of the wires. For example, entering the left ventricle because of dextro transposition of the great arteries after a Senning/Mustard repair or having to pace the right atrium/ventricle from a persistent left sided superior vena cava and the coronary sinus [5]. There were no other similar case reports or research data describing a patient with an elevated left hemidiaphragm leading to a challenging PPM implantation.…”
Section: Discussionmentioning
confidence: 99%
“…If these complications are not treated in a timely manner, the treatment efficacy and prognosis of PPI in patients might be affected, along with the progression of the disease. Therefore, PPI complications have become a focus of research among cardiovascular physicians (12,13). Relevant data have previously shown that the postoperative complication rate of patients with PPI is approximately 8.2-17.4%.…”
Section: Discussionmentioning
confidence: 99%
“…catheter-related [perforation, tear and incorrect positioning] infection and neurological sequelae). 3,4,5…”
Section: Ventricular Assist Devicesmentioning
confidence: 99%
“…Occasionally, because of device malfunction, the body of the HMII may be replaced without changing the outflow graft, and as a result of variations between the new and old designs, complications such as outflow bend relief detachments and kinking may be seen. 5,14…”
Section: Ventricular Assist Devicesmentioning
confidence: 99%